Proposal for the Implementation of Crowdmapping for the Recognition of Social Housing in Urban City Councils - Larrota-Forero, Rafael-Andrés; González-Sanabria, Juan-Sebastián; Sarmiento-Rojas, Jorge-Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Presents a study of crowdmapping as a practice for collaborative mapping in information management in order to make a proposal for the implementation of Crowdmapping within the process of recognition of Social Interest Housing (VIS) carried out by urban curatorships as an alternative in the optimization of internal management processes. For this purpose, a review of the process and data management model of three pioneering and current collaborative platforms in this practice was carried out. The crowdmapping workflow was analyzed and it was integrated into the recognition process to be implemented using a collaborative platform.  The design of tasks, assignment of roles and strategies for data collection were key elements within the workflow in order to develop participatory capabilities in the community and have a shared management with quality. The outcome was a Crowdsourced collaborative map that provides relevant information to officials and administrators of the curatorial offices in the stages of achieving VIS recognition.